The Relationship Between Planned Brand Awareness of Indonesian Radio and Listening Decisions - Magdalena Veriyati; Dini Valdiani; Diana Amaliasari (Penerbit Jurnal Indonesia, 2025)
Most of the This study aims to analyze the relationship between brand awareness and listening decisions of Berencana Radio Indonesia, a streaming radio service by the National Population and Family Planning Board targeting listeners aged 13–40. A quantitative methodology was employed, with data collected through online questionnaires, observations, institutional records, and literature reviews. The Spearman correlation coefficient was used to analyze the data. The results showed that there is a significant relationship between brand awareness and listening decision as indicated by a correlation value of 0.546 and a significance value of 0.000 < 0.05. The brand awareness of Berencana Radio Indonesia is very good, with the average score of each indicator in the very high category. From the results of this research, it is hoped that Berencana Radio Indonesia continues to improve its brand awareness campaign to maintain its existence among listeners.